The Brief Self-Control Scale and Its Refined Version among Incarcerated and Community Youths: Psychometrics and Measurement Invariance. Issue 3 (4th March 2021) - Pechorro, Pedro; DeLisi, Matt; Gonçalves, Rui Abrunhosa; Quintas, Jorge; Hugo Palma, Victor
ABSTRACT: Self-control refers to the ability to override impulses and behave in accordance with societal norms, and deficits in self-control are strongly associated with conduct problems, externalizing disorders, crime, and violence. Here, we examine the psychometric properties of the Brief Self-Control Scale (BSCS) and its refined version (BSCS-R) among a forensic sample ( n = 131) of incarcerated male youth and a school sample of male ( n = 257) and female ( n = 213) youth from Portugal. Confirmatory factor analysis indicated that the original one-factor structure of the BSCS and the refined two-factor structure of the BSCS-R obtained adequate fits. The BSCS demonstrated strong measurement invariance across gender and setting (forensic versus school), while the BSCS-R only revealed gender measurement invariance. The BSCS also tended to perform better that the BSCS-R in terms of other psychometric properties, including internal consistency measured by Alpha and Omega coefficients, discriminant and convergent validities, criterion validity, and known-groups validity. Findings support the use of the BSCS among justice-involved and community youth, but caution is advised regarding the use of its refined version in forensic settings.